Is employment polarisation inevitable? Occupational change in Ireland and Switzerland, 1970-2010 - Murphy, E; Oesch, D (SAGE Publications, 2017)
The routinisation thesis expects technology to hollow out the middle of the employment structure, leading to a uniform pattern of polarisation across affluent countries. This article argues that occupational change is also shaped by labour supply – particularly education and immigration – and institutions. Polarisation therefore represents just one scenario of occupational change. Our study of Ireland and Switzerland examines long-term change in the employment structure (1970–2010), using census data and an encompassing definition of the labour force. Results show no simple trend of occupational upgrading morphing into polarisation. Occupational upgrading occurred in both countries, with the largest employment gains in high-paid occupations and the largest losses in low-paid ones. Patterns of occupational change largely aligned with the evolution of labour supply, upgrading in the 1990s and 2000s being driven in both countries by higher educated women. Immigration supplied labour for low-end and mid-level jobs in Ireland during the Celtic Tiger era, and for low-paid occupations in Switzerland during the 1980s.